Role of Rotifers in Betanodavirus Transmission to European Sea Bass Larvae - Vázquez-Salgado, Lucia; Pascoli, Francesco; Marsella, Andrea; Biasini, Lorena; Buratin, Alessandra; Pretto, Tobia; Abbadi, Miriam; Melchiotti, Erica; Bandín, Isabel; Toffan, Anna (Frontiers in Veterinary Science, 2022)
Marine invertebrates as rotifers or Artemia, frequently used for fish larvae feeding, can be a potential source of pathogens. It has been demonstrated that Artemia can act as an NNV-vector to Senegalese sole larvae. Therefore, in this study we aimed to clarify the role of rotifers in NNV transmission to sea bass larvae following an oral challenge. Our results showed that sea bass larvae fed on a single dose of rotifers retaining NNV displayed clinical signs, mortality, and viral replication similar to the immersion challenge, although the course of the infection was slightly different between the two infection routes. Furthermore, we also demonstrate that rotifers can internalise NNV particles due to their filtering nature and maintain virus viability, since viral particles were detected by immunohistochemistry, immunofluorescence and cell culture within the rotifer body. However, viral quantification data suggested that rotifers are not permissive to NNV replication. In conclusion, this research demonstrated NNV horizontal transmission through rotifers to sea bass larvae, highlighting the importance of establishing strict routine controls on live food to prevent the introduction of potential pathogens to hatcheries.